Cross-Activation of the Motor Cortex during Unilateral Contractions of the Quadriceps - Hendy, Ashlee M.; Chye, Lilian; Teo, Wei-Peng (Frontiers in Human Neuroscience, 2017)
Transcranial magnetic stimulation studies have demonstrated that unilateral muscle contractions in the upper limb produce motor cortical activity in both the contralateral and ipsilateral motor cortices. The increase in excitability of the corticomotor pathway activating the resting limb has been termed ‘cross-activation’, and is of importance due to its involvement in cross-education and rehabilitation. To date, very few studies have investigated cross-activation in the lower limb. To determine the effect of varying contraction intensities in the lower limb, we investigated corticomotor excitability and intracortical inhibition of the right rectus femoris while the left leg performed isometric extension at 0%, 25%, 50%, 75% and 100% of maximum force output. Contraction intensities of 50% maximal force output and greater produced significant cross-activation of the corticomotor pathway. A reduction in silent period duration was observed during 75% and 100% contractions, while the release of short-interval intracortical inhibition was only observed during maximal (100%) contractions. We concluded that increasing isometric contraction intensities produced a monotonic increase in cross activation, which was greatest during 100% force output. Unilateral training programs designed to induce cross-education of strength in the lower limb should therefore be prescribed at the maximal intensity tolerable.